2022
DOI: 10.3389/fimmu.2022.857069
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B Induced ROS-Mediated Autophagy and Th1/Th2 Imbalance via Selenoproteins in Hepa1-6 Cells

Abstract: Schisandrin B (Sch B) is well-known for its antitumor effect; however, its underlying mechanism remains confusing. Our study aimed to investigate the role of selenoproteins in Sch B-induced autophagy and Th1/Th2 imbalance in Hepa1-6 cells. Hepa1-6 cells were chosen to explore the antitumor mechanism and were treated with 0, 25, 50, and 100 μM of Sch B for 24 h, respectively. We detected the inhibition rate of proliferation, transmission electron microscopy (TEM), monodansylcadaverine (MDC) staining, reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Necroptosis has also been shown to be a key driver of inflammation induced by RIPK3 (Zhang et al, 2019b). Meanwhile, Th1/Th2 imbalance caused by overproduction of ROS is also an important factor in cell death (Tan et al, 2022). Qin et al (2020) believed that oxidative stress caused by selenium deficiency could induce windpipe immune damage of chickens by changed the expressions of IFN‐γ, IL‐2, IL‐4, and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis has also been shown to be a key driver of inflammation induced by RIPK3 (Zhang et al, 2019b). Meanwhile, Th1/Th2 imbalance caused by overproduction of ROS is also an important factor in cell death (Tan et al, 2022). Qin et al (2020) believed that oxidative stress caused by selenium deficiency could induce windpipe immune damage of chickens by changed the expressions of IFN‐γ, IL‐2, IL‐4, and IL‐6.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the most significant enrichment of these 273 mRNAs was the Th1 and Th2 cell differentiation (Figure 7d). It has been reported that there is a potential interaction between ROS and Th1/ Th2 imbalance, 30 which may be the potential mechanism of the CeO 2 /BSA nanocluster treatment. GO analysis also showed that differential mRNAs were part of inflammationrelated pathways, including the immunoglobulin complex, immunoglobulin receptor binding, and immune response (Figure S9).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Schisandrin B (Sch B), a compound extracted from Schisandra chinensis, has previously been used to treat liver diseases [7][8][9]. Lately, investigations have claimed the beneficial effect of Sch B against different tumors such as cholangiocarcinoma [10], hepatoma [11], gastric cancer [12], glioma [13], prostate cancer [14], and multi-drug-resistant breast cancer [15]. Research has suggested that Sch B is able to restore the drug sensitivity of multi-drug-resistant MCF-7 cells [15].…”
Section: Introductionmentioning
confidence: 99%